Oasis - Chang-dong, Lee; Choi Yeong-taek; Sul, Kyung-Goo; Moon So-ri; Ahn Nae-sang (Third Window Films, 2009)
Moon So-ri plays a women with cerebral palsy who is ignored and abused in life until simpleton Sol Kyung-gu comes into her life. The idea is simple but the execution for a film like this is difficult. Keeping a film like "Oasis" from being cliché ridden is a mean feat in itself but to turn it into a film as watchable as some of the best Korean romances I've seen is watching a true master at work. You will laugh, you will cry and you will be shocked by what's on screen. The performances by the two leads will endear them to you forever. A film like "Oasis" will make art directors squirm in their seats because it is able to get messages across on so many levels without making audiences go "What the heck"? and yet it is still fresh and original in everyway. [www.dvdbeaver.com]
Keywords: DVD-Video